2024
DOI: 10.1002/smll.202309901
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Mediated Defect Engineering Endows High Reversible Amorphous VS4 Anode for Advanced Sodium‐Ion Storage

Di Zhang,
Yachuan Shao,
Jian Wang
et al.

Abstract: Metal sulfides are promising anode materials for sodium‐ion batteries (SIBs) due to their structural diversity and high theoretical capacity, but the severe capacity decay and inferior rate capability caused by poor structural stability and sluggish kinetics impede their practical applications. Herein, a cobalt‐doped amorphous VS4 wrapped by reduced graphene oxide (i.e., Co0.5‐VS4/rGO) is developed through a Co‐induced defect engineering strategy to boost the kinetics performances. The as‐prepared Co0.5‐VS4/rG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Recently, heteroatom-induced engineering has achieved considerable success in semiconductors and brought interesting characteristics, including polymorphism transformation, regulation of ion/electron conductivity, and reduction of diffusion barrier. Chen et al reported a Mn-doped FeS multicore nanoparticle with enhanced reversible capacity and rate performance due to the high concentration of Mn-heteroatoms doping, which manipulates the electronic structure and improves the charge carrier transport. Meanwhile, Zhang et al fabricated a cobalt-doped amorphous VS 4 with tailored electronic structure, sufficient defects, and abundant active adsorption sites, which may responsible for its improved electronic conductivity as well as accelerated ion mobility. Our previous research has also demonstrated that by rationally introducing vanadium heteroatoms, the intrinsic electronic texture, the charge transfer, and the reversibility of electrode reactions of pristine MoS 2 phase can be modulated synchronously, thus endowing superior Na-storage performances .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, heteroatom-induced engineering has achieved considerable success in semiconductors and brought interesting characteristics, including polymorphism transformation, regulation of ion/electron conductivity, and reduction of diffusion barrier. Chen et al reported a Mn-doped FeS multicore nanoparticle with enhanced reversible capacity and rate performance due to the high concentration of Mn-heteroatoms doping, which manipulates the electronic structure and improves the charge carrier transport. Meanwhile, Zhang et al fabricated a cobalt-doped amorphous VS 4 with tailored electronic structure, sufficient defects, and abundant active adsorption sites, which may responsible for its improved electronic conductivity as well as accelerated ion mobility. Our previous research has also demonstrated that by rationally introducing vanadium heteroatoms, the intrinsic electronic texture, the charge transfer, and the reversibility of electrode reactions of pristine MoS 2 phase can be modulated synchronously, thus endowing superior Na-storage performances .…”
Section: Introductionmentioning
confidence: 99%